Long‐term outcome following pneumatic dilatation as initial therapy for idiopathic achalasia: an 18‐year single‐centre experience. Issue 12 (10th May 2013) - Elliott, T. R.; Wu, P. I.; Fuentealba, S.; Szczesniak, M.; de, D. J.; Cook, I. J.
Summary Background Relapse after treatment for idiopathic achalasia is common and long‐term outcome data are limited. Aim To determine the cumulative relapse rate and long‐term outcome after pneumatic dilatation (PD) for achalasia in a tertiary referral centre. Methods A retrospective study of 301 patients with achalasia treated with PD as first‐line therapy. Short‐term outcome was measured at 12 months. Long‐term outcome was assessed in those who were in remission at 12 months by cumulative relapse rate and cross‐sectional analysis of long‐term remission rate regardless of any interval therapy, using a validated achalasia‐specific questionnaire. Results Eighty‐two percent of patients were in remission 12 months following initial PD. Relapse rates thereafter were 18% by 2 years; 41% by 5 years and 60% by 10 years. Whilst 43% patients underwent additional treatments [PD (29%), myotomy (11%) or botulinum toxin (3%)] beyond 12 months, 32% of those who had not received interval therapy had relapsed at cross‐sectional analysis. After a mean follow‐up of 9.3 years, regardless of nature, timing or frequency of any interval therapy, 71% (79/111) patients were in remission. The perforation rate from PD was 2%. Chest pain had a poor predictive value (24%) for perforation. Conclusions Long‐term relapse is common following pneumatic dilatation. While on‐demand pneumatic dilatation for relapse yields a good response, one‐third of relapsers neither seek medical attention nor receive interval therapy. Close follow‐up with timely repeat dilatation is necessary for a good long‐term outcome. Given the poor predictive value of chest pain for perforation, routine gastrografin swallow is recommended postdilatation.